Screening and Characterization of Proteolytic Thermophiles Bacteria from Moinit Coastal Hot-Spring, North Sulawesi - Elvy Like Ginting (Sam Ratulangi University, 2020)
Thermophilic bacteria have been recognized as the ideal producers of thermostable enzymes and therefore they have a long time become an interesting target for research. Thermophilic proteolytic bacteria from Moinit coastal hot-spring North Sulawesi Indonesia have been isolated and some of them, have been identified and reported. In this research, we reported another eleven thermophilic proteolytic bacteria from Moinit coastal hot-spring, North Sulawesi, Indonesia which designated as 1a, 1b, 2a, 3a, 3b, 4a, 11a, 11b, 16a, 16b, and 16c. Those thermophilic proteolytic bacteria had different colony and cell morphology characteristics, and biochemical characteristics. Bacterial isolate 1a, 1b, 2a, 16a and 16c were Gram negative-bacilli, 3a, 3b and 11b were Gram positive-bacilli, 4a, 11a and 16b were Gram positive-coccus. These bacterial isolates could produce proteolytic activities at 55oC. This showed their ability to produce thermostable protease extracellularly which has the potential to explore biotechnological industries.Keywords: Moinit, protease, screening, thermophilic Â ABSTRAKBakteri termofilik dikenal sebagai produsen enzim termostabil dan menjadi target yang menarik untuk diteliti. Bakteri proteolitik termofil dari sumber air panas pantai Moinit Sulawesi Utara telah berhasil diisolasi dan bahkan 5 isolat bakteri telah diidentifikasi dan dilaporkan. Dalam tulisan ini, diuraikan sebelas isolat bakteri proteolitik termofil lainnya dalam kemampuannya menghasilkan protease dan karakteristik bakteri tersebut. Kesebelas bakteri adalah 1a, 1b, 2a, 3a, 3b, 4a, 11a, 11b, 16b, 16b, 16b, dan 16c yang menunjukkan karakteristik morfologi koloni dan sel bakteri, serta karakteristik biokimia yang berbeda. Isolat 1a, 1b, 2a, 16a, 16c adalah Gram negatif-basil, isolat 3a, 3b, 11b adalah Gram positif-basil, dan isolat 4a, 11a,16b adalah Gram positif-kokus. Keseluruhan isolat bakteri ini memiliki kemampuan aktivitas proteolitik pada 55oC. Hal ini menunjukkan kemampuan bakteri tersebut dalam menghasilkan protease termostabil ekstraseluler yang berpotensi untuk dieksplorasi dalam pemanfaatannya dalam bidang industri bioteknologi.Kata kunci: Moinit, protease, penapisan, termofilik